The Unlawful Acts of Commercial Corporations (With a Focus on Multinational Companies) (El-Wahat Journal for Research and Studies, 2025)
The criminal responsibility of legal persons (in general) and commercial companies (in particular) has garnered attention from both jurisprudence and comparative legislation. This is due to the enormous number of legal entities, whether belonging to the public sector or the private sector, and their dominance over various social and economic activities through their extensive capabilities. This activity can be a source of crimes committed by the natural person managing the legal entity (the commercial company), including crimes such as money laundering, tax evasion, fraud, and even environmental crimes. Given the economic and social importance of commercial companies, especially with the emergence of multinational corporations whose economies exceed those of entire countries, their influence is significant at all political, economic, and social levels. This influence is due to their control of massive production means, capital, and monopolization of modern technology, which countries need at various levels, especially economically. This has turned them into tools of pressure and extortion against many countries and even a violation of their sovereignty.Keywords:Legal Personality, Multinational Companies.